Randomized, double‐blind, phase two study of ruxolitinib plus regorafenib in patients with relapsed/refractory metastatic colorectal cancer. (19th August 2018) - Fogelman, David; Cubillo, Antonio; García‐Alfonso, Pilar; Mirón, María Luisa Limón; Nemunaitis, John; Flora, Daniel; Borg, Christophe; Mineur, Laurent; Vieitez, Jose M.; Cohn, Allen; Saylors, Gene; Assad, Albert; et al.
Abstract: Background: The Janus kinase/signal transducer and activator of transcription (JAK‐STAT) signaling pathway plays a key role in the systemic inflammatory response in many cancers, including colorectal cancer (CRC). This study evaluated the addition of ruxolitinib, a potent JAK1/2 inhibitor, to regorafenib in patients with relapsed/refractory metastatic CRC. Methods: In this two‐part, multicenter, phase 2 study, eligible adult patients had metastatic adenocarcinoma of the colon or rectum; an Eastern Cooperative Oncology Group performance status of 0‐2; received fluoropyrimidine, oxaliplatin, and irinotecan‐based chemotherapy, an anti‐vascular endothelial growth factor therapy (if no contraindication); and if KRAS wild‐type (and no contraindication), an anti‐epidermal growth factor receptor therapy; and progressed following the last administration of approved therapy. Patients who received previous treatment with regorafenib, had an established cardiac or gastrointestinal disease, or had an active infection requiring treatment were excluded. The study was conducted in 95 sites in North America, European Union, Asia Pacific, and Israel. After an open‐label, safety run‐in phase (part 1; ruxolitinib 20 mg twice daily [BID] plus regorafenib 160 mg once daily [QD]), the double‐blind, randomized phase (part 2) was conducted wherein patients were randomized 1:1 to receive ruxolitinib 15 mg BID plus regorafenib 160 mg QD [ruxolitinib group] or placebo plus regorafenib 160 mg QD [placebo group]. Part 2 included substudy 1 (patients with high systemic inflammation, ie, C‐reactive protein [CRP] >10 mg/L) and substudy 2 (patients with low systemic inflammation, ie, CRP ≤10 mg/L); the primary endpoint was overall survival (OS). Results: The study was terminated early; substudy 1 was terminated for futility at interim analysis and substudy 2 was terminated per sponsor decision. Ruxolitinib 20 mg BID was well tolerated in the safety run‐in (n = 11). Overall, 396 patients were randomized (substudy 1: n = 175 [ruxolitinib group, n = 87; placebo group, n = 88]; substudy 2: n = 221 [ruxolitinib group, n = 110; placebo group, n = 111]). There was no significant difference in OS or progression‐free survival (PFS) between treatments in substudy 1 (OS: hazard ratio [HR] = 1.040 [95% confidence interval: 0.725‐1.492]; PFS: HR = 1.004 [0.724‐1.391]) and substudy 2 (OS: HR = 0.767 [0.478‐1.231]; PFS: HR = 0.787 [0.576‐1.074]). The most common hematologic adverse event was anemia. No new safety signals with ruxolitinib were identified. Conclusions: Although addition of ruxolitinib to regorafenib did not show increased safety concerns in patients with relapsed/refractory metastatic CRC, this combination did not improve OS/PFS vs. regorafenib plus placebo. Abstract : The addition of ruxolitinib, a JAK 1/2 inhibitor, to regorafenib was well tolerated in patients with relapsed/refractory metastatic colorectal cancer. However, this combination did not improve survival outcomes compared with regorafenib plus placebo.